The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1980
DOI: 10.1017/s0305000900007054
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between parental input frequencies and children's language acquisition: a reanalysis of Brown's data

Abstract: To evaluate Brown's assertion that frequency of input is not a significant variable in language acquisition, some of Brown's data were reanalysed. The data pertaining to Adam, Eve, Sarah and their parents were predominantly obtained from Brown's (1973) book and were supplemented from the transcripts. Parental input frequency and the children's age at mastery were highly related for each of the three triads. Then Sarah's input and rate of language acquisition were compared with that of the other two children. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
2
3

Year Published

1982
1982
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 6 publications
4
52
2
3
Order By: Relevance
“…The input from Phases I through III has been subdivided into Phase I and Phases II-III to see whether the input frequency for each form is consistent over time. If there is inconsistency, that is, if a given form is noticeably more frequent in one particular phase, we wanted to see whether there is a correlation between high frequency at a given time and the time of acquisition (Cross 1977, Moerk 1980). A first look at the data suggests that the 7 suffixes can be divided into three groups in terms of relative frequency.…”
Section: Formmentioning
confidence: 99%
“…The input from Phases I through III has been subdivided into Phase I and Phases II-III to see whether the input frequency for each form is consistent over time. If there is inconsistency, that is, if a given form is noticeably more frequent in one particular phase, we wanted to see whether there is a correlation between high frequency at a given time and the time of acquisition (Cross 1977, Moerk 1980). A first look at the data suggests that the 7 suffixes can be divided into three groups in terms of relative frequency.…”
Section: Formmentioning
confidence: 99%
“…These results are consistent with previous findings on the relationship between maternal and child frequency of forms. Moerk (1980) reports a correlation of .66 between mother-child frequencies of certain forms in Roger Brown's data, and Fomer (1977), even stronger correlations between mother-child frequency of wh-questions: .87/.98 in her German data and .91 in Savid's Serbo-Croatian data.…”
Section: The Role Of Maternal Frequencymentioning
confidence: 90%
“…English grammatical morphemes: Forner (1979) and Moerk (1980) reanalyzed Brown's (1973) data on the input frequency of these morphemes and found that the order of acquisition can be predicted not only by linguistic complexity but equally well by input frequency (see also Wolff, 1988, p. 201).…”
Section: Confounding Of the Effect Of Simplicity And Input Frequency mentioning
confidence: 99%